How restaurant influencers’ characteristics impact Gen Z’s restaurant visit: an elaboration likelihood perspective - Priya Pereira; Senthilkumaran Piramanayagam; Jyothi Mallya; Vidya Patwardhan (Cogent Business & Management)
This study examines the role of restaurant influencers’ (RI) characteristics on Gen Z’s attitudes and visits to the recommended restaurants using the Elaboration Likelihood Model approach. A quantitative survey using an online structured questionnaire was used to collect the data from 331 respondents. Structural equation modelling was used to appraise the hypothesized relationships among the constructs. The findings revealed that RIs’ credibility, authenticity, interactivity, and playfulness significantly impact their followers’ attitudes toward the restaurant. However, the originality and likeability of the RIs did not significantly impact Gen Z’s attitudes. The findings also demonstrated that Gen Z’s visit intention has a significant positive impact on their restaurant visits. The findings of this study are helpful for the restaurant marketing industry, managers, and influencers to develop a powerful brand image, awareness, and direct customer relationships.